Per Jacobsson Lecture #1. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper reports about the Per Jacobsson Foundation and various lectures in detail. Mr. Camdessus was educated at the University of Paris and earned postgraduate degrees in economics at the Institut d'Etudes Politiques de Paris and at the Ecole Nationale d'Administration Publique. He is a member of the Commission for Africa, which is chaired by the British Prime Minister, Tony Blair. Following his appointment as Administrateur Civil in the French Civil Service, Mr. Camdessus joined the Treasury in the Ministry of Finance in I960. After serving as Financial Attache to the French delegation at the European Economic Community in Brussels from 1966 to 1968, he returned to the Treasury and went on to become Assistant Director in 1971, Deputy Director in 1974, and Director in February 1982. Mr. Camdessus was appointed as Managing Director and Chairman of the Executive Board of the IMF on January 16, 1987. On May 22, 1996, the Executive Board of the IMF unanimously selected him to serve a third five-year term as Managing Director, beginning January 16, 1997.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banque De France; Former Managing Director Of The IMF2imf; Governor Of The IMF; Managing Director Of The IMF; PJ; France